SIMULASI PENGUKURAN LONGSOR PADA KELERENGAN DAN KEDALAMAN BIDANG GELINCIR YANG BERBEDA - Pilya Tri Oktafiani; Sri Rahayu Utami; Christanti Agustina (Jurnal Tanah dan Sumberdaya Lahan, 2022)
Landslide is one of the geological disasters that often occurs in Indonesia. Landslides can be caused by several factors; there are human factors and natural factors. In principle, landslides occur when the resisting force is smaller than the driving force. Landslides on a small and large scale can occur over time and have a fairly severe impact. Therefore, this study simulated the effect of slope and depth of slip surface on the duration and volume of landslides, which are simulated on two soils with different texture classes. Landslide simulations were conducted at Agro Techno Park and The Experimental Gardens Faculty of Agriculture. The simulation used eight treatments and ten replications consisting of three factors there are soil texture, slope and depth of slickenside. Landslide simulation was conducted using an acrylic box with a size of 100 cm x 50 cm x 75 cm with rain intensity 70 mm hour-1. The variables measured are landslides duration, landslides volume, soil texture and bulk density. Data analysis used an independent sample t-test. The result showed slope and slickenside have a significant effect on landslides duration and landslides volume. The greater the slope, the landslide occurs faster on landslides duration and the greater the volume of the landslide. The deeper slickenside has a longer landslides duration, but the volume of the landslide is larger. It showed that the greater slope has a smaller influence on the depth of slickenside and soil texture on the landslides duration and landslides volume.